Direct Stimulation by Methanol Addition on the Cultured Medium for Methanol Dehydrogenase Protein Purification from Bradyrhizobium japonicum USDA110 - Novita Kurniawati; Ambar Pertiwiningrum; Yuny Erwanto; Nanung Agus Fitriyanto; Mohammad Zainal Abidin (Faculty of Animal Science, Universitas Gadjah Mada, 2018)
Methanol dehydrogenase (MDH) enzyme was purified from Bradyrhizobium japonicum USDA110 cell-free extract. The bacteria were grown in a culture medium with direct 0.5% methanol addition aimed to stimulates the MDH catalytic enzyme activation. Bradyrhizobium japonicum USDA110 MDH enzyme was purified by using 25 mM 2-(N-morpholine) ethanesulfonic acid/MES pH 5.5 buffer and 1 M sodium chloride/NaCl which separated into three columns, the first column was PD-10 for buffer exchange; the second column was HiTrap Sepharose HP to obtain unbonded fraction in the column; and the third column was Mono S 5/50 GL integrated with two pumps HPLC (high-performance liquid chromatography) to obtain pure MDH enzyme for serial changing of 1 M NaCl-25mM MES pH 5.5 with the flow rate at 1 ml/min. The protein concentration and MDH catalytic enzyme activity were observed on each purification process starting from the cell-free extract to pure MDH enzyme. The pure MDH enzyme was obtained by Mono S 5/50 GL-HPLC purification which showed a single band on SDS PAGE (sodium dodecyl sulfate-polyacrylamide gel electrophoresis). The MDH enzyme purification from Bradyrhizobium japonicum USDA110 showed 90-fold purification, a sub-molecular weight of 63 kDa, specific activity at 2.69 U/mg, and optimum activity at a 35oC temperature and pH 9.